A closed-form solution in piezo-viscous squeeze films between a long cylinder and an infinite plate. Issue 3 (8th April 2014) - Lin, Jaw-Ren; Lu, Rong-Fang
Abstract : Purpose: – The aim of this study is to extend the squeezing film problems between a long cylinder and an infinite plate, considering the piezo-viscous behavior (PVB) of the Barus experimental relationship. Design/methodology/approach: – By integrating the nonlinear Reynolds-type differential equation directly, an analytical film-pressure solution is obtained and applied to investigate the load-carrying capacity and the approaching time. Findings: – Compared with the case of constant-viscosity lubricants (CVLs), the effects of PVB are found to provide higher load-carrying capacities and longer approaching times for the squeezing films. Originality/value: – It is found that when the cylinder is squeezed to a dimensionless central film height of 0.3, the dimensionless approaching time required for the CVL case is 4.922. However, the effects of PVB (α 0.0001, 0.001, 0.005 and 0.01) provide longer approaching times with values of 8.324, 8.438, 9.028 and 10.079. The cylinder-plate squeeze film system considering the influences of PVB results in a longer operating life.